PACKING OF CYLINDRICAL PARTICLE MIXTURES - Iniyatova, Gulfairuz (School of Engineering and Digital Sciences, 2023)
Particle packing is significant in manufacturing and chemical engineering. Packing densification by vibration is an important process that affects product storage, transportation, and processing. However, most previous research has focused on the vibrational packing of binary mixtures of spherical particles, while a large part of the powders used in everyday life and industrial production have a non-spherical shape. Therefore, this work aims to study the influence of the shape of the cylindrical particles on the packing structure of binary mixtures and the effect of vibration conditions on packing density. Packings of binary mixtures of cylindrical particles with different aspect ratios and volume fractions were generated under gravity. In the first part of the study, the impact of the aspect ratio and volume fraction of cylindrical particles on the packing microstructure was studied. The findings demonstrate that mixtures with particles with a high aspect ratio and mixtures with a high percentage of elongated cylindrical particles produce less dense packings. The intensity of vibration alone cannot adequately characterize the influence of vibration on the packing structure. The second part of the research work was prioritized to consider the impact of vibration amplitude and frequency on the packing density of the mixture. The amplitude range varied between 0.004-0.012 m at a constant frequency of 50 rad/s, and the frequency was between 50-150 rad/s at a constant amplitude of 0.006 m. The total packing density of three mixtures was calculated for each vibrational condition. As a result, the densification was obtained for the binary mixture with the volume fraction of 50:50 at conditions A=0.006 m, ω= 50 rad/s. With the increase of amplitude and frequency, particles of mixture over-exited leading to a loose packing structure. It was not possible to reach the densification at given vibration conditions for binary mixtures with volume fractions of 25:75 and 75:25. This is explained by the change in particle orientation. To confirm that, a histogram of the angle between the horizontal plane and the particle axes was demonstrated. It was found that after applying vibrational forces particles change their position and tend to orientate vertically, which creates voids and lower packing density. To study the impact of aspect ratio and volume fraction of the cylindrical particles and the influence of vibration conditions on binary mixtures in more detail packing fractions of mixtures were analyzed by the voxelization method. The planar packing fraction curves reveal that the lowest packing fraction is produced by a mixture of 75% elongated particles and 25% cylinders with AR=1. Packing fraction along the x and y directions demonstrated the displacement of the particles to one side of the wall at high vibration amplitude or frequency leading to an increase in bed height and a decrease in the packing density. The vibration amplitude and frequency do not significantly change the packing fraction of bottom particles, while top particles over-excite, forming loose packing. In conclusion, the microstructure of binary mixtures of cylindrical particles with different volume fractions and aspect ratios was studied. The packing density of mixtures was analyzed at different vibration conditions. According to the simulation results, the percentage of elongated particles in a binary mixture can influence the packing structure and the vibration amplitude and frequency can significantly affect the packing density of binary cylindrical particle mixtures by changing the orientation of cylindrical particles in the packing.
Keywords: type of access: open access; cylindrical particle mixtures